Marine Collagen-Based Bioink for 3D Bioprinting of a Bilayered Skin Model - Aida Cavallo; Tamer Al Kayal; Angelica Mero; Andrea Mezzetta; Anissa Pisani; Ilenia Foffa; Cecilia Vecoli; Marianna Buscemi; Lorenzo Guazzelli; Giorgio Soldani; Paola Losi (Pharmaceutics, 2023)
Marine organisms (i.e., fish, jellyfish, sponges or seaweeds) represent an abundant and eco-friendly source of collagen. Marine collagen, compared to mammalian collagen, can be easily extracted, is water-soluble, avoids transmissible diseases and owns anti-microbial activities. Recent studies have reported marine collagen as a suitable biomaterial for skin tissue regeneration. The aim of this work was to investigate, for the first time, marine collagen from basa fish skin for the development of a bioink for extrusion 3D bioprinting of a bilayered skin model. The bioinks were obtained by mixing semi-crosslinked alginate with 10 and 20 mg/mL of collagen. The bioinks were characterised by evaluating the printability in terms of homogeneity, spreading ratio, shape fidelity and rheological properties. Morphology, degradation rate, swelling properties and antibacterial activity were also evaluated. The alginate-based bioink containing 20 mg/mL of marine collagen was selected for 3D bioprinting of skin-like constructs with human fibroblasts and keratinocytes. The bioprinted constructs showed a homogeneous distribution of viable and proliferating cells at days 1, 7 and 14 of culture evaluated by qualitative (live/dead) and qualitative (XTT) assays, and histological (H&E) and gene expression analysis. In conclusion, marine collagen can be successfully used to formulate a bioink for 3D bioprinting. In particular, the obtained bioink can be printed in 3D structures and is able to support fibroblasts and keratinocytes viability and proliferation.